Shorter lunch breaks lead secondary-school students to make less healthy dietary choices: multilevel analysis of cross-sectional national survey data. Issue 9 (5th September 2014) - Townsend, Nicholas
Abstract: Objective: At the time of the study a number of schools within Wales had shortened the amount of time they allow for lunch break. The study investigated the association between length of lunch break and the dietary choices of students in secondary schools. Design: Student-level data, collected through anonymised questionnaires, included reported dietary choices and correlates of these; data on school approaches to food were collected through postal surveys. Multilevel analysis was used to study the independent association between lunch-break length and student dietary choice. Setting: Data were collected from secondary schools in Wales that were part of the 2005/2006 Health Behaviour in School-aged Children (HBSC) study. Subjects: The final sample for analysis included data from 6693 students aged 11–16 years and 289 teachers from sixty-four secondary schools in Wales. Results: Once controlling for many individual-level and school-level factors, the length of time allowed for lunch across the range for schools included in the study (minimum =25 min, maximum =62·5 min) was associated with higher odds of students eating fruit for lunch (2·20; 95 % CI 1·18, 4·11) and fruit and vegetables on a daily basis (2·15; 95 % CI 1·33, 3·47) but lower odds of eating unhealthy foods on a daily basis (0·44; 95 % CI 0·24, 0·80). Conclusions: Shorter lunch breaks are associated with less healthy dietary choices by students. Schools should consider the impact that lunch-break length has on student dietary choice as well as on other behaviours. Policy makers should work with schools in encouraging them to maintain lunch breaks of a length that allow pupils to make healthy choices.